Safe Maternity Units and Perinatal High Reliability. Issue 2 (March 2021) - Simpson, Kathleen Rice
Abstract : A recent study on features of safe maternity units is remarkably similar to findings from 20 years ago on perinatal high reliability units. The same aspects of patient safety for maternity units are still valid, yet unsafe practice conditions continue. A summary of current and historical aspects of safe care for mothers and babies in the inpatient setting is presented.